Therapeutic Potential of Pterostilbene and Resveratrol on Biomechanic, Biochemical, and Histological Parameters in Streptozotocin-Induced Diabetic Rats. (16th May 2018) - Tastekin, Bora; Pelit, Aykut; Polat, Sait; Tuli, Abdullah; Sencar, Leman; Alparslan, Mustafa Muhlis; Daglioglu, Yusuf Kenan
Abstract : Aims . The aim of this study was to investigate the effects of pterostilbene (PTS) (trans-3, 5-dimethoxy-4′-hydroxystilbene) and resveratrol (RSV) (trans-3, 5, 4′ trihydroxystilbene) applied at different doses for the treatment of streptozotocin- (STZ-) induced diabetic rats. Materials and Methods. At the end of the 5-week experimental period, the right gastrocnemius muscles of the rats were examined biomechanically, while the left ones were examined histologically. In addition, blood glucose, serum insulin, and malondialdehyde (MDA) levels were analyzed in blood samples taken from the rats. Results . The skeletal muscle isometric contraction forces, which showed a decrease with diabetes, were observed to increase with antioxidant applications. Blood glucose, serum insulin, and MDA levels in diabetic rats approached normal levels after applying PTS. When the electron microscopic images of the rat skeletal muscle were examined, those in the combination treatment group were observed to show a better enhancement in the skeletal muscle morphological structure compared to the other diabetic and treatment groups. Conclusion . According to the findings, we suggest that these antioxidant treatments might have good therapeutic nutraceutical potential for some muscle diseases that coexist with diabetes. These treatments should be comprehensively investigated in the future.